Positive electrode active material for sodium secondary battery, method for preparing same, and sodium secondary battery comprising same

By mixing and firing P2 particles and O3 particles, Na migration is induced and the Na content ratio is controlled, the problems of large structural changes in the positive electrode active substances of sodium ion secondary batteries are solved, and high initial capacity and excellent life characteristics are achieved.

CN119920891APending Publication Date: 2025-05-02ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411209262.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-31
Filing Date
2024-08-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The structure of the positive electrode active substance of the existing sodium ion secondary battery changes greatly during the charging and discharging process, resulting in a decrease in cycling stability and making it difficult to maintain the initial capacity and life characteristics.

Method used

By mixing and firing P2 particles and O3 particles, Na migration is induced from the surface of O3 oxide particles to the surface of P2 oxide particles, and the ratio of the surface Na content of O3 layered oxide particles to the surface of P2 layered oxide particles is controlled to improve cell performance.

Benefits of technology

The positive electrode active substance with excellent initial capacity and excellent service life characteristics is achieved, the cycle stability and structural stability of the battery are improved, and the side reactions of the electrolyte and gas generation are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920891A_ABST
    Figure CN119920891A_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode active material for a sodium secondary battery, a method for preparing the same, and a sodium secondary battery comprising the positive electrode active material, the positive electrode active material for a sodium secondary battery being characterized by containing P2-type layered oxide particles and O3-type layered oxide particles, and having a specific surface area of at least one of the P2-type layered oxide particles and the O3-type layered oxide particles in scanning electron microscope-X-ray spectrometer (SEM-EDS) mapping analysis, the specific surface area of the P2-type layered oxide particles being less than the specific surface area of the O3-type layered oxide particles being less than the specific surface area of the O3-type layered oxide particles. The ratio S3 / S2 of the surface Na content (at%) S3 of the O3-type layered oxide particles to the surface Na content (at%) S2 of the P2-type layered oxide particles is 0.4 to 1.6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material for a sodium secondary battery, a preparation method thereof and a sodium secondary battery comprising the positive electrode active material. Background Art

[0002] Lithium-ion secondary batteries are widely used as energy storage devices in various electronic technology fields. Recently, as the demand for lithium-ion secondary batteries has increased dramatically, sodium-ion secondary batteries have attracted much attention as a substitute for expensive metal lithium. Sodium-ion secondary batteries have a working principle similar to the insertion / extraction reaction of lithium-ion secondary batteries, and are therefore one of the next-generation materials with high potential for application in secondary batteries.

[0003] As the positive electrode active material of the sodium ion secondary battery, a layered transition metal oxide is used. The layered transition metal oxide has a representative simple structure and excellent electrochemical performance and is easy to synthesize. Generally, compared with P2-type layered oxide particles, O3-type layered oxides have higher energy density, but their disadvantage is that they cause greater structural changes during charging and discharging, resulting in reduced cycle stability. Although P2-type layered oxides have relatively excellent cycle stability, they are difficult to commercialize due to their low sodium content and relatively low energy density.

[0004] Mixed particles of P2-type oxide particles and O3-type oxide particles exist at the same time. The O3-type layered oxide provides a higher discharge capacity, and the P2-type layered oxide suppresses the structural changes caused by the release of more sodium ions, in an attempt to develop products with excellent initial capacity and excellent life characteristics.

[0005] However, it is difficult to ensure the target battery performance by simply using a mixed phase. When the O3-type oxide particles are washed with water to remove the residual Na on the particle surface, the internal Na escapes completely, making it difficult to improve the problem of being unable to maintain the structure. As a result, it is difficult to solve the problem of reduced battery life and stability, such as gas generation due to electrolyte side reactions during battery operation, reduced capacity and output of the positive electrode active material, due to the presence of sodium byproducts on the particle surface in the form of Na2CO3 and NaOH. Summary of the invention

[0006] Technical problem to be solved by the invention

[0007] The object of the present invention is to prepare P2 type particles and O3 type particles, mix them and sinter them, thereby inducing Na migration from the surface of O3 type oxide particles to the surface of P2 type oxide particles, so as to provide a positive electrode active material having excellent initial capacity and excellent life characteristics based on the mixed use of P2 type particles and O3 type particles.

[0008] In addition, the purpose of the present invention is to improve the problem of particle structure collapse and phase transformation of O3 type particles to P3 type by controlling the ratio S3 / S2 of the surface Na content (at%) S3 of O3 type layered oxide particles to the surface Na content (at%) S2 of P2 type layered oxide particles.

[0009] In addition, an object of the present invention is to provide a technology for selectively adjusting only the surface Na content of each of the P2 type particles and the O3 type particles while maintaining the total Na equivalent.

[0010] Means for solving technical problems

[0011] One example of the present invention provides a positive electrode active material for a sodium secondary battery, which is characterized in that it contains P2-type layered oxide particles and O3-type layered oxide particles, and in a scanning electron microscope-X-ray energy dispersive spectrometer (SEM-EDS) mapping analysis, the ratio S3 / S2 of the surface Na content (at%) S3 of the O3-type layered oxide particles to the surface Na content (at%) S2 of the P2-type layered oxide particles is 0.4 to 1.6.

[0012] A ratio S3 / S2 of a surface Na content (at %) S3 of the O3 type layered oxide particles to a surface Na content (at %) S2 of the P2 type layered oxide particles may be 0.65 to 1.45.

[0013] In a scanning electron microscope-X-ray energy dispersive spectrometer (SEM-EDS) mapping analysis, the surface Na content (at%) S2 of the P2-type layered oxide particles may be 14.5 at% to 21.5 at%, and the surface Na content (at%) S3 of the O3-type layered oxide particles may be 7.5 at% to 21.5 at%.

[0014] The surface Na content (at%) S2 of the P2 type layered oxide particles may be 14.5 at % to 21.5 at %, and the surface Na content (at %) S3 of the O3 type layered oxide particles may be 14.5 at % to 21.5 at %.

[0015] The P2 type layered oxide may be represented by the following Chemical Formula 1, and the O3 type layered oxide may be represented by the following Chemical Formula 2.

[0016] Chemical formula 1: Na a [Ni x M1 y Mn 1-x-y ]O2

[0017] In the chemical formula 1, M1 is at least one selected from P, Sr, Ba, Ti, Zr, W, Co, Mg, Al, Cu, Zn, Ce, Hf, Ta, F, Cr, V, Si, Fe, Y, Ga, Sn, Mo, Ge, Nd, B, Nb and Gd, and 0.44<a<0.80, 0.05≤x≤0.45, 0.05≤y≤0.15, and 0.45<1-xy≤0.9.

[0018] Chemical formula 2: Na a [Ni x M1 y M2 z Mn 1-x-y-z ]O2

[0019] In the chemical formula 1, M1 is at least one selected from the group consisting of Fe and Mn, M2 is at least one selected from P, Sr, Ba, Ti, Zr, W, Co, Mg, Al, Cu, Zn, Ce, Hf, Ta, F, Cr, V, Si, Fe, Y, Ga, Sn, Mo, Ge, Nd, B, Nb and Gd, and 0.80<a<1.1, 0.05≤x≤0.45, 0.05≤y≤0.45, 0.05≤z≤0.15, and 0.05<1-xyz≤0.45.

[0020] The Na equivalent (Na / M ratio) of the P2 type layered oxide may be 0.60 to 0.70, and the Na equivalent (Na / M ratio) of the O3 type layered oxide may be 0.90 to 1.05.

[0021] The P2 type layered oxide particles and the O3 type layered oxide particles may be included in a weight ratio of 8:2 to 2:8.

[0022] According to X-ray diffraction (XRD) analysis, the positive electrode active material may not have a NiOx peak.

[0023] The residual Na content (Total Sodium, TTS) of the positive electrode active material may be 500 ppm to 10000 ppm.

[0024] The positive electrode active material may be prepared by mixing P2 type layered oxide particles and O3 type layered oxide particles and firing the mixed oxide particles.

[0025] Another embodiment of the present invention provides a method for preparing a positive electrode active material for a sodium secondary battery, wherein the method is characterized in that P2-type layered oxide particles and O3-type layered oxide particles are mixed and the mixed oxide particles are sintered.

[0026] Before the sintering, the P2 type layered oxide particles and the O3 type layered oxide particles may not be washed with water to remove residual Na on the surface.

[0027] The P2 type layered oxide particles and the O3 type layered oxide particles may be mixed in a weight ratio of 8:2 to 2:8.

[0028] The sintering may be performed at a temperature of 400° C. to 1000° C. for 3 hours to 16 hours.

[0029] Another example of the present invention provides a positive electrode for a sodium secondary battery including a positive electrode active material and a sodium secondary battery including the positive electrode and a negative electrode.

[0030] Effects of the Invention

[0031] According to the present invention, the P2 type particles can replenish the Na on the particle surface lost due to water washing or due to the overall low Na content, and the O3 type particles can effectively remove the residual Na without causing structural collapse.

[0032] In addition, regardless of the adjustment of the total Na equivalent, the O3 type oxide particles basically have low structural stability. Therefore, when water washing is performed to remove residual Na, there is a problem that the structure cannot be maintained because all the internal Na escapes. However, in the present invention, the residual Na of the O3 type oxide particles can be effectively removed.

[0033] In addition, in the present invention, by controlling the transition of Na migration (Namigration) from O3 type oxide particles to P2 type oxide particles, the problem of the particle structure of O3 type particles collapsing and transforming into P3 type particles can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figures 1a to 2b Example 1 ( Figure 1a , 1b ) and Example 3 ( Figure 2a , 2b ) before and after the second sintering of the mixed P2-type oxide particles and O3-type oxide particles prepared in the process of FIG. 5 . The results of SEM-EDS mapping analysis of the particle surface are shown in FIG. 5 .

[0035] Figure 3 These are the X-ray diffraction peak (XRD peak) analysis results before and after sintering (second sintering) after mixing the P2-type oxide particles and the O3-type oxide particles prepared in Examples 1 to 3.

[0036] Figure 4It is a measurement graph of the residual Na content (TTS) before and after the second calcination, and a measurement graph of the first charge capacity (CH), the first discharge capacity (DCH) and the initial efficiency (ICE).

[0037] Figure 5 It is the result of XRD peak shift analysis of the positive electrode active material based on whether the second sintering is suitable at different temperatures.

[0038] Figure 6 This is a life characteristic analysis chart of sodium secondary batteries based on whether they are suitable for secondary firing at different temperatures.

[0039] Figure 7 This is a graph showing the measurement of gas generation in the sodium secondary battery according to whether or not the second firing was used in Example 1. DETAILED DESCRIPTION

[0040] The advantages and features of the present invention, and methods for achieving them, will become clear when referring to the embodiments described in detail below together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below, but can be implemented in various forms, and the embodiments are provided to make the disclosure of the present invention complete and to fully inform the scope of the invention to those skilled in the art to which the present invention belongs. The present invention is defined only by the scope of the scope of the invention.

[0041] Unless otherwise defined, all terms (including technical terms and scientific terms) used in this specification can be used as meanings that can be commonly understood by ordinary technicians in the technical field to which the present invention belongs. Throughout the specification, unless otherwise specifically described to the contrary, when a part "includes" a certain constituent element, it means that other constituent elements may also be included, rather than excluding other constituent elements. In addition, unless otherwise mentioned in a sentence, the singular form also includes the plural form.

[0042] One embodiment of the present invention provides a positive electrode active material for a sodium secondary battery. The positive electrode active material comprises P2-type layered oxide particles and O3-type layered oxide particles.

[0043] As is known to all, the disadvantage of P2-type layered oxides is that they have excellent life characteristics due to structural stability, but have low initial capacity due to low Na content, and the disadvantage of O3-type layered oxides is that they have low initial capacity due to high Na content, but have reduced structural stability, and due to the slightly smaller size of the octahedral site where Na may be located in the structure, the Na movement speed is low, and the life characteristics are reduced. In the present invention, a positive electrode active material that maintains the advantages of each particle and improves the disadvantages can be provided by mixing P2-type and O3-type layered oxide particles and sintering them.

[0044] The positive electrode active material of the present invention is characterized in that, in the scanning electron microscope-X-ray energy dispersive spectrometer (SEM-EDS) mapping analysis, the ratio S3 / S2 of the surface Na content (at%) S3 of the O3 type layered oxide particles to the surface Na content (at%) S2 of the P2 type layered oxide particles is 0.4 to 1.6.

[0045] This structural characteristic is the result of separately preparing P2-type particles and O3-type particles, mixing and firing them to induce Na migration from the surface of O3-type oxide particles to the surface of P2-type oxide particles. As a result, P2-type particles can replenish the Na on the particle surface lost due to water washing or due to the overall low Na content, and O3-type particles can effectively remove residual Na without causing structural collapse.

[0046] Unlike the present invention, even if the particles are prepared by increasing the total Na equivalent of the P2 type particles and reducing the total Na equivalent of the O3 type particles, it is difficult to control the surface Na content ratio of the O3 / P2 particles within the range of the present invention when considering the fact that the Na equivalent range is limited in order to maintain the P2 phase and the O3 phase, and that it is difficult to selectively adjust only the surface Na content while maintaining the total Na equivalent. In addition, regardless of the adjustment of the total Na equivalent, the structural stability of the O3 type oxide particles is basically low, and therefore, when washing with water to remove the residual Na, there is a problem that the structure cannot be maintained because all the internal Na escapes, but in the present invention, the residual Na of the O3 type oxide particles can be effectively removed.

[0047] Specifically, when the ratio S3 / S2 of the surface Na content (at%) S3 of the O3 type layered oxide particles to the surface Na content (at%) S2 of the P2 type layered oxide particles is 0.65 to 1.45, it may be desirable. When the S3 / S2 ratio is too low, Na migration from the O3 type oxide particles to the P2 type oxide particles proceeds excessively, so that the particle structure of the O3 type particles collapses and there is a possibility of phase transformation to the P3 type.

[0048] In the scanning electron microscope-X-ray energy dispersive spectrometer (SEM-EDS) element mapping analysis, the surface Na content (at%) S2 of the P2 type layered oxide particles can be 14.5 at% to 21.5 at%, specifically, 15 to 21 at%, 16 to 20 at%, or 17 to 19 at%. In addition, the surface Na content (at%) S3 of the O3 type layered oxide particles can be 7.5 at% to 21.5 at%, specifically, 8 to 21 at%, 14.5 to 21.5 at%, 15 to 21 at%, 16 to 20 at%, or 17 to 19 at%. Therefore, the above-mentioned effects can be further improved.

[0049] When the surface Na content of P2 and O3 type layered oxides exceeds the design range, the residual Na content can be increased in proportion. Therefore, within the upper voltage range (~4.3V), there is a risk of electrolyte side reactions and increased gas generation caused by residual Na. On the contrary, when the surface Na content is lower than the design range, the internal Na present on the particle surface may escape, and there may be a problem of not being able to maintain the crystalline structure.

[0050] On the other hand, the scanning electron microscope-X-ray energy spectrometer (SEM-EDS) element mapping analysis can be analyzed at a voltage intensity of 10kV to 20kV, preferably, at a voltage intensity of 15kV. According to the set voltage intensity, the depth (area) and target elements can be specifically detected (detecting) from the surface to the interior of the particle. In the present invention, the X-ray energy spectrometer (EDS) element mapping analysis is performed at a voltage intensity within the design range to determine the change in the surface Na atomic% of P2 type and O3 type particles under the same analysis conditions. At this time, the surface of the particle can be slightly changed according to the voltage intensity, and the present invention is not limited to a specific depth (length, area).

[0051] The P2 type layered oxide may be represented by the following Chemical Formula 1, and the O3 type layered oxide may be represented by the following Chemical Formula 2.

[0052] Chemical formula 1: Na a [Ni x M1 y Mn 1-x-y ]O2

[0053] In the chemical formula 1, M1 is at least one selected from P, Sr, Ba, Ti, Zr, W, Co, Mg, Al, Cu, Zn, Ce, Hf, Ta, F, Cr, V, Si, Fe, Y, Ga, Sn, Mo, Ge, Nd, B, Nb and Gd, and 0.44<a<0.80, 0.05≤x≤0.45, 0.05≤y≤0.15, and 0.45<1-xy≤0.9.

[0054] When the Na equivalent of the P2-type layered oxide is less than 0.44 (a≤0.44), the oxide has a three-dimensional tunnel structure, and the electrochemical properties may be deteriorated depending on the arrangement of the lattice unit. On the contrary, when the Na equivalent is greater than 0.80 (0.80≤a), the oxide has a layered O3 structure, which has the disadvantages of reduced atmospheric and moisture stability and sensitivity to synthesis conditions such as temperature and atmosphere.

[0055] Chemical formula 2: Na a [Ni x M1 y M2 z Mn 1-x-y-z ]O2

[0056] In the chemical formula 1, M1 is at least one selected from the group consisting of Fe and Mn, M2 is at least one selected from P, Sr, Ba, Ti, Zr, W, Co, Mg, Al, Cu, Zn, Ce, Hf, Ta, F, Cr, V, Si, Fe, Y, Ga, Sn, Mo, Ge, Nd, B, Nb and Gd, and 0.80<a<1.1, 0.05≤x≤0.45, 0.05≤y≤0.45, 0.05≤z≤0.15, and 0.05<1-xyz≤0.45.

[0057] When the Na equivalent of the O3-type layered oxide is less than 0.80 (a<0.80), the oxide has a P3-type structure, and the electrochemical properties may be deteriorated depending on the arrangement of the lattice unit. On the contrary, when the Na equivalent is greater than 1.10 (0.10≤a), there are disadvantages such as decreased stability to the atmosphere and moisture, and sensitivity to synthesis conditions such as temperature and atmosphere.

[0058] The Na equivalent (Na / M ratio) of the P2 type layered oxide may be 0.60 to 0.70, and the Na equivalent (Na / M ratio) of the O3 type layered oxide may be 0.90 to 1.05. Therefore, the above-mentioned effects can be further improved.

[0059] The P2-type layered oxide particles and the O3-type layered oxide particles can be contained in a weight ratio of 8:2 to 2:8. Specifically, preferably, it is 8:2 to 4:6, 8:2 to 5:5 or 8:2 to 6:4 by weight. When the content of O3-type particles is slightly low, the overall capacity characteristics will deteriorate. On the contrary, when it is slightly high, even if Na migration is performed, the residual Na content will be high, and there is a possibility of forming a thick cathode-electrolyte interface (CEI) and a reduction in initial efficiency (ICE) and the possibility of gas generation. In addition, when the above-mentioned preferred content range is met, an initial efficiency (ICE) of more than 90% and sufficient capacity characteristics can be ensured.

[0060] The positive electrode active material may be characterized by the absence of a NiOx peak in an X-ray diffraction (XRD) analysis. NiOx crystalline phases are easily synthesized on the surface of the P2 type particles lost due to water washing or due to a low overall Na content, but in the present invention, the surface of the P2 type particles can be supplemented by Na migration through O3 type particles, thereby preventing the synthesis of crystalline phases such as NiOx.

[0061] The positive electrode active material of the present invention can reduce the residual Na content (Total Sodium, TTS) to 500ppm to 10000ppm, specifically, to 500-9500ppm, 500-9000ppm, 1000-9000ppm or 5000-9000ppm. Therefore, the gas generation caused by the residual Na can be suppressed, and the battery life characteristics can be significantly improved.

[0062] On the other hand, the residual Na content (Total Sodium, TTS) may be a value (Total Sodium, TTS) obtained by calculating only the total amount of Na in a compound containing residual Na (eg, NaOH or Na2CO3).

[0063] Another embodiment of the present invention provides a method for preparing a positive electrode active material for a sodium secondary battery, characterized in that P2-type layered oxide particles and O3-type layered oxide particles are mixed and the mixed oxide particles are sintered.

[0064] The particles may be mixed in the weight ratio as described above, and any mixing method may be used without limitation as long as it is a method known in the relevant technical field.

[0065] The P2 type layered oxide particles and the O3 type layered oxide particles are as described above, and may be used without limitation as long as they are particles obtained by methods known in the relevant technical field.

[0066] On the other hand, the P2-type layered oxide particles may be particles that have been washed with water to remove residual Na on the surface, and the O3-type layered oxide particles may be particles that have not been washed with water to remove residual Na on the surface. The P2-type layered oxide has high structural stability and can be washed with water, but the O3-type layered oxide is more likely to collapse in structure during washing with water and is therefore difficult to wash with water.

[0067] In addition, preferably, the P2-type layered oxide particles and the O3-type layered oxide particles are not washed with water to remove residual Na on the surface. To this end, for the P2-type layered oxide particles, the P2 structure is synthesized with a low Na equivalent (0.65, 0.60, 0.55, etc.), and in order to supplement the insufficient Na, in the subsequent second sintering step, the surface Na migration (Na migration, which moves Na from a high concentration to a low concentration) phenomenon of the O3-type layered oxide is utilized.

[0068] The sintering of the mixed oxide particles can be carried out at a temperature of 400 to 1000°C for 4 to 16 hours, specifically, at a temperature of 500 to 1000°C, a temperature of 600 to 1000°C, a temperature of 700 to 1000°C in an air atmosphere for 6 to 16 hours, 8 to 16 hours, or 10 to 14 hours.

[0069] When the sintering temperature or sintering time is lower than the lower limit, the desired phase may not be sufficiently synthesized, and when it exceeds the upper limit, Na that has entered the crystal lattice may dissolve out of the surface again.

[0070] Through the process described above, Na migration can be performed from the surface of O3-type oxide particles to the surface of P2-type oxide particles. As a result, P2-type particles can replenish the Na on the particle surface lost due to water washing or due to the overall low Na content, and O3-type particles can effectively remove residual Na without structural collapse, thereby improving battery performance such as capacity characteristics, efficiency characteristics, and life characteristics.

[0071] Another example of the present invention provides a positive electrode for a sodium secondary battery and a sodium secondary battery including the positive electrode active material.

[0072] The positive electrode includes a positive electrode collector and a positive electrode active material layer on the positive electrode collector, and the positive electrode active material according to one aspect of the present invention is present in the positive electrode active material layer.

[0073] As long as the positive electrode collector does not cause chemical changes to the battery and has conductivity, there is no particular limitation, for example, it can be surface treated with carbon, nickel, titanium, silver, etc. on stainless steel, aluminum, nickel, titanium, plastic carbon or aluminum or stainless steel surface. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and the bonding force of the positive electrode active material can also be improved by forming micro-concave and convex on the collector surface. These positive electrode collectors can be provided in various forms, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0074] In addition, the positive electrode active material layer may be a layer containing a conductive material and a binder together with the above-mentioned positive electrode active material.

[0075] Among them, the conductive material is used to give conductivity to the electrode. As long as it does not cause chemical changes in the positive electrode active material and has conductivity, it can be used without special restrictions. As non-limiting examples of conductive materials, there are graphites such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polystyrene derivatives. Usually based on the total weight of the positive electrode active material layer, it can contain 1% to 30% by weight of conductive material.

[0076] In addition, the binder is a material for improving the adhesion between the positive active material particles and the bonding force between the positive active material and the collector. As a non-limiting example of the binder, there is polyvinylidene fluoride (PVDF), poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated-ethylene propylene diene monomer rubber (EPDM), styrene butadiene rubber (SBR), fluororubber, or its various copolymers. Typically, based on the total weight of the positive active material layer, 1% to 30% by weight of the binder may be included.

[0077] In addition to using the above-mentioned positive electrode active material, the positive electrode according to one example of the present invention can be prepared according to the preparation method of the positive electrode for a conventional sodium secondary battery. For example, the positive electrode active material and the selective slurry containing a binder and a conductive material for forming a positive electrode active material layer are applied to the positive electrode collector, and then dried and rolled, so that the positive electrode can be prepared. According to another example, the slurry for forming the positive electrode active material layer is cast on a separate support, and then the positive electrode active material layer is peeled off from the support, and the obtained film is laminated on the positive electrode collector, so that the positive electrode can be prepared.

[0078] According to another aspect of the present invention, an electrochemical device comprising the above-mentioned positive electrode is provided, wherein the electrochemical device may specifically be a battery, a capacitor, etc., and more specifically may be a sodium secondary battery.

[0079] The sodium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator between the positive electrode and the negative electrode, and an electrolyte (electrolyte). In addition, the sodium secondary battery may include a battery container (shell) for accommodating an electrode assembly, and a sealing member for sealing the battery container, wherein the electrode assembly includes a positive electrode, a negative electrode, and a separator.

[0080] At this time, sodium secondary batteries can be classified into can type sodium secondary batteries in which the electrode assembly is built into a metal can and pouch type sodium secondary batteries in which the electrode assembly is built into a pouch formed of a sheet such as an aluminum laminate, according to the shape of the battery container (casing).

[0081] In particular, for a pouch-type sodium secondary battery using a positive electrode including a positive electrode active material according to various embodiments of the present invention, since the possibility of a side reaction between the positive electrode active material and the electrolyte is small, it has the advantage of improving stability during storage and / or operation while reducing gas generation.

[0082] Hereinafter, the present invention will be described in detail by way of examples. However, this is for further illustrating the present invention in detail, and the scope of protection claimed by the present invention is not limited to the following examples.

[0083] Example

[0084] (Example 1)

[0085] In Ni 0.35 Mn 0.65 The sodium compound Na2CO3 with Na / M=0.65 equivalent was added to the (OH)2 precursor and sintered at 950°C for 6 hours in an air atmosphere to prepare P2-type layered oxide particles (Na 0.65 Ni 0.35 Mn 0.65 O2 powder).

[0086] In Ni 0.33 Fe 0.33 Mn 0.33 The sodium compound Na2CO3 with Na / M=1.05 equivalent was added to the (OH)2 precursor and sintered at 950°C for 12 hours in an air atmosphere to prepare O3-type layered oxide particles (Na 1.05 Ni 0.33 Fe 0.33 Mn 0.33 O2 powder).

[0087] The prepared P2-type oxide particles and O3-type oxide particles were mixed at a weight ratio of 7:3 and fired for a second time at 800° C. for 6 hours in an air atmosphere to prepare a positive electrode active material.

[0088] 30 g of the prepared positive electrode active material 96 wt%, carbon black 2 wt%, polyvinylidene fluoride (PVdF) binder 2 wt% were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was uniformly coated on an aluminum film with a thickness of 15 μm and vacuum dried at 135° C. to prepare a positive electrode for a sodium secondary battery.

[0089] For the positive electrode, a sodium metal plate was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separation membrane, and a sodium secondary battery (button cell) was prepared using an electrolyte containing NaPF6 at a concentration of 1.15 M in a solvent in which ethyl carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7.

[0090] (Examples 2-3)

[0091] When preparing P2-type layered oxide particles, in addition to preparing Na with Na / M=0.55 equivalents (Example 2) and 0.45 equivalents (Example 3), 0.55 Ni 0.35 Mn 0.65 O2 (Example 2) Na 0.45 Ni 0.35 Mn 0.65 O2 (Example 3) particles were added, and the same method as in Example 1 was used to prepare a positive electrode active material and a sodium secondary battery.

[0092] Experimental example

[0093] Experimental Example 1: Scanning Electron Microscope-Energy Dispersive Spectrometer (SEM-EDS) Mapping of Positive Electrode Active Material Particles (mapping) analysis

[0094] After the P2-type oxide particles and the O3-type oxide particles prepared in Example 1 and Example 3 were mixed, a scanning electron microscope-X-ray energy dispersive spectrometer (SEM-EDS) mapping analysis of the particle surface before and after the second sintering was performed at a voltage intensity of 15 kV.

[0095] (Example 1) Before / after the second firing: Figure 1a / Figure 1b

[0096] (Example 3) Before / after the second firing: Figure 2a / Figure 2b

[0097] Table 1

[0098]

[0099] refer to Figure 1a and 1b (Example 1) Figure 2a and 2b (Example 3) In Example 1 and Example 3, after sintering, the Na migration phenomenon from the surface of the O3-type oxide particles to the surface of the P2-type oxide particles was confirmed. The residual Na of the O3-type particles was migrated to the surface of the P2-type particles by the second sintering, and it was confirmed that the P2-type particles can replenish the Na on the particle surface lost due to water washing, and the O3-type particles can effectively remove the residual Na without structural collapse.

[0100] Referring to Table 1, for Example 1, the Na content ratio of the surface of the O3 type particles / P2 type particles is reduced from 1.67 to 2.6 to 0.7 to 1.4 after sintering, which is lower than the Na equivalent ratio of the entire particle (O3 type particles / P2 type particles as a whole) of 1.62. Therefore, it is confirmed that the P2 type particles are supplemented with Na on the surface to improve the problem of low initial capacity caused by low Na in the past, and the O3 type particles stably reduce Na on the surface without particle surface defects or structural collapse, thereby improving the problem of low Na movement speed caused by the small size of the octahedral site where Na can be located in the past. In addition, it also has the effect of improving the problems of electrolyte side reactions and gas generation caused by the reduction of residual Na.

[0101] In Example 3, it was confirmed that Na migration was slightly excessive after the second calcination, and the Na content ratio of the O3 type particle / P2 type particle surface was reduced to a slightly lower range of 0.4 to 0.93. As a result, the particle structure of the O3 type particle collapsed and could be transformed into the P3 type.

[0102] Experimental Example 2: XRD peak shift analysis

[0103] The X-ray diffraction peak (XRD peak) analysis was performed before and after sintering (second sintering) after mixing the P2-type oxide particles and the O3-type oxide particles prepared in Examples 1 to 3. The results are shown in Tables 2 and 3 below. Figure 3 middle.

[0104] Reference Figure 3The migration phenomenon can be proved from the XRD shift results. The residual Na on the surface of O3 enters the P2 structure, causing the P2 (002) peak to move to the right (high angle). During the heat treatment process, not only the residual Na of O3 moves, but also part of the Na in the O3 lattice moves, so the (003) peak of the O3 structure moves to the left (low angle). Therefore, the stability of each structure of P2 and O3 can be improved.

[0105] The final Na / M equivalent of P2 calculated from the (002 plane) peak shift (increase) of P2 type particles converges to 0.68-0.66 in Examples 1-3, and the final Na / M equivalent of O3 calculated from the (003 plane) peak shift (decrease) of O3 type particles converges to 0.9-1.0.

[0106] However, the lower the Na equivalent of the P2 type particles, the more Na migration from the O3 type particles to the P2 type particles tends to increase when the P2 / O3 particles are mixed and sintered. When the P2 type particles have a Na0.45 equivalent, Na migration (Namigration) proceeds excessively, and the structure of the O3 type particles is expected to collapse.

[0107] Experimental Example 3: Battery Performance Evaluation Based on the Mixing Ratio of P2-Type Particles and O3-Type Particles

[0108] A positive electrode active material and a sodium secondary battery were prepared in the same manner except that the P2 type particles and the O3 type particles were prepared at the mixing ratio described in Table 2 below in Example 1.

[0109] The residual Na content (TTS) before and after the second calcination was measured, and the first charge capacity (CH), first discharge capacity (DCH) and initial efficiency (ICE) of the sodium secondary battery were measured and are shown in Tables 2 and Figure 4 .

[0110] * Determination of residual Na content (TTS)

[0111] The residual sodium content is determined by potentiometric neutralization titration of each compound containing residual Na (eg, NaOH or Na2CO3), and then the total amount of Na alone is calculated as the total sodium (TTS).

[0112] The calculation method is shown in the following formula 1.

[0113] Formula 1:

[0114] TTS (Total Na) = NaOH analysis value (%) × Na / NaOH + Na2CO3 analysis value (%) × 2Na / Na2CO3

[0115] *Battery performance evaluation

[0116] The battery was charged / discharged once at 0.1C / 0.5C at 25°C and a driving voltage range of 2.0V to 4.6V, and the first (1st) charge capacity, first (1st) discharge capacity, and first (1st) discharge / charge capacity (ICE) were calculated.

[0117] Table 2

[0118]

[0119] Refer to Table 2 and Figure 4 When the content of O3 particles is lower than 20wt%, the capacity characteristics are poor. On the contrary, when the content of O3 particles is higher than 80wt%, the residual Na content is too high, and there is a possibility of forming a thick cathode-electrolyte interface (CEI), a decrease in initial efficiency (ICE), and the possibility of gas generation.

[0120] In addition, in order to ensure an initial efficiency (ICE) of more than 90% and sufficient capacity characteristics, the P2 / O3 mixing ratio may preferably be designed to be 8 / 2 to 6 / 4 by weight.

[0121] Experimental Example 4: XRD peak shift and life span according to the change of the second firing temperature Life characteristics evaluation

[0122] A positive electrode active material and a sodium secondary battery were prepared in the same manner as in Example 1, except that the second calcination was performed at the temperature described in Table 3 below.

[0123] The XRD peak shift analysis results of the prepared positive electrode active material before and after the second calcination at various temperatures are shown in Tables 3 and Figure 5 middle.

[0124] The battery life characteristics before and after the second firing at various temperatures were analyzed and shown in Figure 6 middle.

[0125] *Battery life characteristics

[0126] For the battery life characteristics, an electrochemical analyzer (Toscat-3100, manufactured by Toyo, Japan) was used to perform 50 charge / discharge cycles at 1C / 1C at 25°C and a driving voltage range of 2.0V to 4.6V. The ratio of the discharge capacity to the initial capacity in 1 to 50 cycles (cycle capacity retention) was then measured.

[0127] Table 3

[0128]

[0129] Refer to Table 3. Figure 5 and Figure 6 When the second calcination is performed at 750 to 900° C., which is a preferred second calcination temperature range, an X-ray diffraction shift (XRD shift) due to Na migration is confirmed.

[0130] On the other hand, when the temperature is lower than the design temperature, no migration effect occurs. When the temperature is higher than the design temperature, high temperature sintering may cause structural degradation of the positive electrode active material. Both P2 and O3 oxides may cause Na in the crystal lattice to return to the surface again, causing the crystal structure to collapse.

[0131] Experimental Example 5: Analysis of gas generation from the second firing

[0132] After mixing the P2 type particles and the O3 type particles in Example 1, the following experimental results 1) to 4) are shown for each of the sodium secondary battery prepared by the positive electrode active material prepared without applying the second calcination (before calcination) and the sodium secondary battery prepared by applying the positive electrode active material prepared by applying the second calcination (after calcination). Figure 7 middle.

[0133] 1) After the first (1st) C / D: The gas (Gas) generated after the first charge / discharge after assembling the battery (Cell) was measured.

[0134] 2) After De-gas: The gas generated after the first charge / discharge is extracted.

[0135] 3) After the second to third (2nd to 3rd) C / D: The gas generated after the charge / discharge in the formation step was measured.

[0136] 4) After 50 cycles: After the second to third C / D, the volume was assumed to be 0, and the gas generated after 50 cycles was measured.

[0137] Reference Figure 7 It was confirmed that when the second firing of the present invention is performed, the gas production can be reduced by removing the residual Na, compared with the case where the firing is not performed.

[0138] As described above, the present invention illustrates and describes specific embodiments, but it is self-evident to those skilled in the art that the present invention can be variously modified and changed without departing from the technical concept of the present invention provided by the scope of protection of the attached invention claims.

Claims

1. A positive electrode active material for a sodium secondary battery, characterized in that comprising P2-type layered oxide particles and O3-type layered oxide particles, In the scanning electron microscope-X-ray spectrometer mapping analysis, the ratio S3 / S2 of the surface Na content (at%) S3 of the O3 type layered oxide particles to the surface Na content (at%) S2 of the P2 type layered oxide particles is 0.4 to 1.

6.

2. The positive electrode active material for sodium secondary battery according to claim 1, characterized in that The ratio S3 / S2 of the surface Na content (at%) S3 of the O3 type layered oxide particles to the surface Na content (at%) S2 of the P2 type layered oxide particles is 0.65 to 1.

45.

3. The positive electrode active material for sodium secondary battery according to claim 1, characterized in that In the scanning electron microscope-X-ray spectrometer mapping analysis, the surface Na content (at%) S2 of the P2 type layered oxide particles is 14.5at% to 21.5at%, and the surface Na content (at%) S3 of the O3 type layered oxide particles is 7.5at% to 21.5at%.

4. The positive electrode active material for sodium secondary battery according to claim 3, characterized in that: The surface Na content (at%) S2 of the P2 type layered oxide particles is 14.5 at % to 21.5 at %, and the surface Na content (at %) S3 of the O3 type layered oxide particles is 14.5 at % to 21.5 at %.

5. The positive electrode active material for sodium secondary battery according to claim 1, characterized in that: The P2-type layered oxide is represented by the following Chemical Formula 1, and the O3-type layered oxide is represented by the following Chemical Formula 2: Chemical formula 1: Na a [Ni x M1 y Mn 1-x-y ]O2 In the chemical formula 1, M1 is at least one selected from P, Sr, Ba, Ti, Zr, W, Co, Mg, Al, Cu, Zn, Ce, Hf, Ta, F, Cr, V, Si, Fe, Y, Ga, Sn, Mo, Ge, Nd, B, Nb and Gd, and 0.44<a<0.80, 0.05≤x≤0.45, 0.05≤y≤0.15, 0.45<1-xy≤0.9, Chemical formula 2: Na a [Ni x M1 y M2 z Mn 1-x-y-z ]O2 In the chemical formula 1, M1 is at least one selected from the group consisting of Fe and Mn, M2 is at least one selected from P, Sr, Ba, Ti, Zr, W, Co, Mg, Al, Cu, Zn, Ce, Hf, Ta, F, Cr, V, Si, Fe, Y, Ga, Sn, Mo, Ge, Nd, B, Nb and Gd, and 0.80<a<1.1, 0.05≤x≤0.45, 0.05≤y≤0.45, 0.05≤z≤0.15, and 0.05<1-xyz≤0.

45.

6. The positive electrode active material for sodium secondary battery according to claim 1, characterized in that The Na equivalent of the P2-type layered oxide, i.e., the Na / M ratio, is 0.60 to 0.

70. The Na equivalent of the O3-type layered oxide, ie, the Na / M ratio, is 0.90 to 1.

05.

7. The positive electrode active material for sodium secondary battery according to claim 1, characterized in that: The P2 type layered oxide particles and the O3 type layered oxide particles are included in a weight ratio of 8:2 to 2:

8.

8. The positive electrode active material for sodium secondary battery according to claim 1, characterized in that: X-ray diffraction analysis shows that the positive electrode active material does not have a NiOx peak.

9. The positive electrode active material for sodium secondary battery according to claim 1, characterized in that: The residual Na content (Total Sodium, TTS) of the positive electrode active material is 500 ppm to 10000 ppm.

10. The positive electrode active material for sodium secondary battery according to claim 1, characterized in that The positive electrode active material is prepared by mixing P2 type layered oxide particles and O3 type layered oxide particles and firing the mixed oxide particles.

11. A method for preparing a positive electrode active material for a sodium secondary battery, characterized in that: Mixing P2-type layered oxide particles and O3-type layered oxide particles, The mixed oxide particles are sintered.

12. The method for preparing a positive electrode active material for a sodium secondary battery according to claim 11, characterized in that: Before the sintering, the P2 type layered oxide particles and the O3 type layered oxide particles are not washed with water for removing residual Na on the surface.

13. The method for preparing a positive electrode active material for a sodium secondary battery according to claim 11, characterized in that: The P2 type layered oxide particles and the O3 type layered oxide particles are mixed in a weight ratio of 8:2 to 2:

8.

14. The method for preparing a positive electrode active material for a sodium secondary battery according to claim 11, characterized in that: The sintering is performed at a temperature of 400° C. to 1000° C. for 3 hours to 16 hours.

15. A positive electrode for a sodium secondary battery, characterized in that: Contains the positive electrode active material according to claim 1.

16. A sodium secondary battery, characterized in that: The method comprises the positive electrode according to claim 15 and a negative electrode.